2013
DOI: 10.1007/s10877-013-9487-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the nociception level: a multi-parameter approach

Abstract: The aim of the present study was to develop and validate an objective index for nociception level (NoL) of patients under general anesthesia, based on a combination of multiple physiological parameters. Twenty-five patients scheduled for elective surgery were enrolled. For clinical reference of NoL, the combined index of stimulus and analgesia was defined as a composite of the surgical stimulus level and a scaled effect-site concentration of opioid. The physiological parameters heart rate, heart rate variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 42 publications
5
137
0
4
Order By: Relevance
“…The linear combination of parameters significantly differentiated not only between pain and no pain, but also between all levels of pain (P < .001 to .02). Similarly Ben-Israel et al [18] developed and validated an index for nociception levels of patients under general anesthesia. The combination of the physiological parameters heart rate (HR), heart rate variability (HRV), PPG wave amplitude, GSR level, and GSR fluctuations outperformed any individual parameter in the evaluation of the nociceptive response.…”
Section: ) Videomentioning
confidence: 99%
“…The linear combination of parameters significantly differentiated not only between pain and no pain, but also between all levels of pain (P < .001 to .02). Similarly Ben-Israel et al [18] developed and validated an index for nociception levels of patients under general anesthesia. The combination of the physiological parameters heart rate (HR), heart rate variability (HRV), PPG wave amplitude, GSR level, and GSR fluctuations outperformed any individual parameter in the evaluation of the nociceptive response.…”
Section: ) Videomentioning
confidence: 99%
“…These include the heart rate, HRV at 0.15-to 0.4-Hz band power, photoplethysmography wave amplitude, skin conductance level, and derivatives [43] , which all represent the activity of the sympathetic nervous system. A systematic review demonstrated an increase in sympathetic activity and a decrease in parasympathetic activity during experimentally induced pain in healthy adults based on HRV measurements [44] .…”
Section: Discussionmentioning
confidence: 99%
“…However, increases in sympathetic activity can be caused by other factors not related to pain. Combinations of previous methods have also been described as potential indicators of nociceptive response as described by Schneider [14] or Ben-Israel [15]. Changes in pupil size [16,17] or other HRV derived parameters studying parasympathetic activity [18] in response to opioid concentrations or noxious stimulation have also been proposed as methods to assess the level of analgesia in surgical patients.…”
Section: Introductionmentioning
confidence: 99%